2021
DOI: 10.1098/rstb.2019.0727
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and sociality: why, when and how does sociality change ageing patterns?

Abstract: Individual lifespans vary tremendously between and also within species, but the proximate and ultimate causes of different ageing speeds are still not well understood. Sociality appears to be associated with the evolution of greater longevity and probably also with a larger plasticity of the shape and pace of ageing. For example, reproductives of several termites and ants reach lifespans that surpass those of their non-reproductive nestmates by one or two decades. In this issue, 15 papers explore the interrela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 87 publications
1
25
0
Order By: Relevance
“…As a result, when social behaviour is age-dependent, it has the potential to modulate how fitness prospects change with age. Understanding the underlying causes of late-life changes in social behaviour is therefore important as social ageing may have the potential to either delay or accelerate other patterns of senescence [ 23 , 26 ]. For instance, we might expect that social ageing resulting from declines in bodily systems will lead to loss of important social relationships, resulting in negative fitness consequences in later life and therefore further exacerbating the rate of senescence.…”
Section: Challenges In Disentangling Drivers Of Social Ageing In Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, when social behaviour is age-dependent, it has the potential to modulate how fitness prospects change with age. Understanding the underlying causes of late-life changes in social behaviour is therefore important as social ageing may have the potential to either delay or accelerate other patterns of senescence [ 23 , 26 ]. For instance, we might expect that social ageing resulting from declines in bodily systems will lead to loss of important social relationships, resulting in negative fitness consequences in later life and therefore further exacerbating the rate of senescence.…”
Section: Challenges In Disentangling Drivers Of Social Ageing In Mammalsmentioning
confidence: 99%
“…It is therefore apparent that sociality, as with many traits, has the potential to show substantial variation in how it is expressed across the adult lifespan [4,22] and may have important downstream effects on other aspects of behaviour, physiology and life history. Yet while much attention has been given to understanding how sociality affects ageing patterns in animals [23][24][25][26][27], comparatively little work has looked at how senescence or other patterns of ageing affect late-life changes in social behaviour. There are well-established agebased changes in physiology, cognition, experience, and life history that might contribute to social ageing [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Hamilton's model assumed an infinite population in which individuals do not interact. A recent themed issue in Philosophical Transactions B ‘ Ageing and sociality: why, when and how does sociality change ageing patterns?’ [77] is testament to a growing interest that such interactions between individuals could alter the evolution of senescence [78]. Given the strong relationship between the social environment and mortality risk in humans [79], it is perhaps not surprising that researchers have now begun to focus their attention on trying to test for similar phenomena in other social animals.…”
Section: Why and Where Species May Not Senescementioning
confidence: 99%
“…These studies have shown that actuarial senescence may favour reduced juvenile dispersal with increasing maternal age [85], that reduced dispersal may favour the evolution of shorter lifespans [86], and that in some scenarios, actuarial senescence can actually be favoured in viscous populations [87,88]. In general, however, a comprehensive ageing theory of social animals is lacking [77].…”
Section: (C) Social Interactionsmentioning
confidence: 99%
“…Furthermore, there appears to be a positive fecundity-longevity relationship within each caste, such that, in eusocial Hymenoptera, the most reproductive queens and workers (which can reproduce asexually in some species) live longer than the least reproductive queens and workers, respectively 1526 . Therefore, it has been suggested that, in eusocial insects, queens (and reproductive workers) represent an exception to the usual negative fecundity-longevity relationship seen in other species, through not exhibiting costs of reproduction 22,24,27 . This apparent reversal of the conventional trade-off has been hypothesised to result from a remodelling of the conserved genetic and endocrine networks that regulate ageing and reproduction 13,2833 .…”
Section: Introductionmentioning
confidence: 99%